Morphometry and Molecular Identification of Haemonchus Cobb, 1898 (Trichostrongylidae: Nematoda) Isolates from Small Ruminants in Tanzania Based on Mitochondrial cox 1 and rRNA-ITS genes. (16th January 2023) - Ndosi, Barakaeli Abdieli; Lee, Dongmin; Bia, Mohammed Mebarek; Yang, Heejae; Hong, Min-Ji; Seo, Sungbo; Park, Hansol; Eom, Keeseon S.
Abstract : The genus Haemonchus is the major abomasal parasite of ruminants responsible for substantial economic losses in tropical and temperate regions. This study was conducted to clarify the morphometry and molecular characterisation of Haemonchus species isolated from sheep in Babati district, Tanzania. A total of 486 trichostrongylid nematodes were recovered from five sheep. Of the total worms, 106 nematodes were distinguished by 37 males and 69 females. The asymmetrical length of dorsal ray and the distance of bulb at the apex of spicules were used for identification of males. In females, the linguiform vulvar flap was the most predominant with 33 out of 69 (48%) compared with knobbed morph type which was 25/69 (36%) and smooth morph type with 11/69 (16%). Partial cox 1 sequence fragments of Haemonchus contortus isolates showed 98.8%, 99.3%, 99.7%, 99.5%, 99.3%, and 98.4% in male, smooth, knobbed, linguiform A, linguiform B, and linguiform C, respectively; with the average nucleotide divergence ranged from 1.03 to 2.35%. The amplified fragments of ITS-2 genes in knobbed, linguiform A, and smooth morphotypes revealed 99.4%, 98.5%, and 98.3%, respectively. Phylogenetic analysis was evaluated by employing Bayesian inference and maximum-likelihood, and the tree was distinctly separated into three clusters focusing on H. contortus in cluster I within the family Haemonchidae. Genetic drifting, mutation, and modification of the morphological features of the Haemonchus species described to have an impact on the development of drug resistance. Species identification is necessary to understand which species infect animal host. We recommend more studies on the parasites intensity and the strategies for controlling Haemonchus species in Tanzania.